Pemberdayaan Kelompok Wanita Tani (KWT) Anggrek Desa Jatisari Melalui Pelatihan dan Pemanfaatan Digitalisasi - Yuyut Prayuti; Atqia, Daris Yusyfa; Anisa Fitriyani; Ummul Munawarah; Meri Indriyani; Alyani Agustina (LPPM UNINUS, 2023)
Empowerment is a process of developing, becoming independent, self-sufficient, strengthening the bargaining position of the lower levels of society towards large-scale entrepreneurs in various fields, with the aim of being able to make society self-sufficient. One of the empowerment initiatives carried out by the government to reduce poverty is by building MSMEs. The use of digital technology is a factor that can advance various sectors, especially the MSME sector. One of the MSME sectors that uses digital technology is the Anggrek Women Farmers Group (KWT) in Jatisari Village, Tanjungsari District, Sumedang Regency. KWT Anggrek has products that are processed themselves by utilizing harvest and livestock products. The KWT product marketing process uses the WhatsApp platform by marketing to local residents. The marketing process, which is only for local residents, has an impact on KWT Anggrek's income which tends to be low. In order for sales to increase, a digital-based marketing strategy is needed to expand the market. Based on the conditions faced by the KWT women, community service was carried out in the form of empowering women farmer groups through training and the use of digitalization. The method used is descriptive qualitative through interview observation and interactive discussions (program socialization). This service began with observations of Jatisari village and KWT Anggrek. Then community empowerment was carried out from several sectors, namely economics, agriculture, law and technology. Mentoring and coaching the MSME community by empowering the Jatisari Village Orchid KWT succeeded in getting a positive response from the community, this can be seen from the enthusiastic presence of the community in various programs. The programs that were successfully carried out were socialization regarding digital marketing, trade law and consumer protection law, training on planting using the hydroponic method, creating digital financial reports, creating websites and social media in the form of Instagram and Facebook for product promotion media that can reach consumers more widely. It is hoped that the success of the Jatisari village digitalization program will develop and be able to reach consumers outside Jatisari Village so that the profits generated can increase